Repair of experimentally induced femoral chondral defect in a rabbit model using Lyophilized growth promoting factor extracted from horse blood platelets (L-GFequina). Issue 4 (April 2022) - Abd El-Rahman, Sahar S.; Amer, Mohammed S.; Hassan, Marwa H.; Fahmy, Hossam M.; Shamaa, Ashraf A.
Highlights: Lyophilized equine platelets derived growth factor (LGF) could repair chondoral defect. LGF lowered the pro-inflammatory cytokines; TNF-α and IL-1β. LGF increased the anabolic and angiogenic growth factors; PDGF and TGF-β1. LGF elevated the expression of chondrogenic-related marker genes; Col I and Col II. LGF decreased the immune-expression of NF-κB p65 and MMP2 proteins. LGF improved the histopathological alterations in osteoarthritis. Abstract: Lyophilized equine platelet derived growth factors (LGF) is a novel advanced platelet rich protein growth factor. It has been successfully applied in various fields of regenerative medicine to treat a variety of inflammatory and degenerative musculoskeletal conditions. Our study aimed to evaluate the efficacy of intraarticularly injected LGF for the remedy of articular cartilage injury, commonly characterized by progressive pain and loss of joint function in osteoarthritic rabbits. Full-thickness cylindrical cartilage defects were generated in both femoral condylar articular surfaces in twenty rabbits. The left joint of all animals was injected with the adjuvant as a self-control negative, while the right joint was injected by LGF. Four- and eight-weeks post-surgery, the femoral condyles were harvested, and assessed grossly, microscopically and immunohistochemically. Cytokines (TNF-α, IL-1β, PDGF and TGF-β1) contents of the chondral defects were quantified by ELISA as well as the gene expression of Col I and Col II via RT-qPCR. The LGF treated defects showed significant higher ICRS (International cartilage repair society) healing scores of cartilaginous regeneration with a significant higher histological healing score on using O'Driscoll histological scoring system. Additionally, LGF significantly lowered the levels of the pro-inflammatory cytokines TNF-α and IL-1β. It also significantly increased the anabolic and angiogenic growth factors (PDGF and TGF-β1), and significantly elevated the expression of chondrogenic-related marker genes; Col I and Col II. The current study reveals that LGF improves chondral healing and thus it can be a superior nominee as an adjunctive therapy to positively influence regeneration of chondral defects in osteoarthritic patients.